ANALISIS PERFORMA KOLEKTOR SURYA PELAT DATAR DENGAN SIRIP MELINTANG BERONGGA DISUSUN ALIGNED MENGGUNAKAN ALIRAN IMPINGING JET - Tulak, Zefanya Farel; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2024)
Abstract The crucial role of renewable energy, particularly solar energy, in human life cannot be underestimated. One notable application is in the agricultural sector as a source of power for crop drying processes. To enhance the effectiveness of solar drying, a device known as a solar collector is required. This collector functions as a absorber of solar radiation, which is then converted into heat energy and transferred to a working fluid. To maximize heat transfer to the working fluid, fins are added to the solar collector to increase its capacity in absorbing trapped heat. Research on these solar collectors involves the addition of hollow fins in the form of square-shaped triangles with smaller diameters, placed inside, arranged in parallel using an impinging jet flow. To enhance the performance of the solar collector, variations in mass flow rates at a temperature of 32 °C are applied, namely 0.0009; 0.0019; and 0.0023 kg/s. The research results indicate that the use of solar collectors with hollow square-shaped fins arranged in parallel using an impinging jet flow leads to an increase and distribution of temperature across each component of the solar collector. The highest useful energy is achieved at a mass flow rate variation of 0.0023 kg/s, with a value of 67.58 W at 13:30, and the highest efficiency is recorded at 14:00 at 10.02%. Meanwhile, the lowest useful energy is observed at a mass flow rate variation of 0.0009 kg/s, with a value of 3.23 W at 10:00, and the lowest efficiency is observed at a mass flow rate variation of 0.0019 kg/s at 10:00, at 1.70%. Keywords: Useful energy, Efficiency, Hollow fin, Aligned, Impinging Jet, Hollow reduced diameter